EVALUATION OF DIGITAL TRANSFORMATION STRATEGY OF TELKOM HUB IN ENHANCING COMPETITIVENESS IN THE TELECOMMUNICATION INDUSTRY - Salsa Kira Husnanda; Zahra Zahira Alamsyah; Beta Melinda Santy; Fahran Eka Putra; Marsya Zahrina (International Journal of Small and Medium Enterprises and Business Sustainability, 2025)
This study aims to analyze the strategic position and determine the most appropriate business strategy for PT Telkom Indonesia in facing the rapid development of the digital telecommunications industry. The research employs a qualitative-descriptive approach using strategic management tools, including the Internal Factor Evaluation (IFE) matrix, External Factor Evaluation (EFE) matrix, SWOT analysis, and the Quantitative Strategic Planning Matrix (QSPM). The results show that Telkom has a robust internal condition with an IFE score of 3.53, supported by its extensive infrastructure, strong brand reputation, and integrated digital ecosystem. Meanwhile, the EFE score of 3.12 indicates that the company effectively leverages external opportunities, such as the increasing demand for digital services, cloud computing, and cybersecurity, despite facing intense competition and rapid technological shifts. The SWOT analysis suggests that Telkom is in a highly competitive position, enabling the pursuit of aggressive growth strategies alongside operational efficiency improvements. Based on the QSPM analysis, the "Restructuring and Efficiency Strategy" is identified as the most attractive option with a Total Attractiveness Score (TAS) of 7.27, slightly outperforming the "Integrated Digital Expansion Strategy" (TAS of 7.02). This study concludes that enhancing internal efficiency, organizational agility, and cost optimization should be the strategic priorities for Telkom to strengthen its competitiveness and sustain long-term growth in the digital era.